PENGALAMAN ANAK JALANAN PERSPEKTIF GENDER DAN KETAHANAN - Nuraidah, Nuraidah (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2023)
This study examines the experiences of street children in Jambi from the perspective of gender and resilience, with the aim of understanding how gender roles affect their experiences and survival strategies. Using a qualitative approach, this research involves in-depth interviews, participatory observations, and documentation analysis. The results showed that boys and girls faced different challenges and developed specific adaptation strategies based on their gender roles. Solidarity and social networks among street children play an important role in their resilience strategies. However, while these strategies are effective in the short term, street children remain in vulnerable conditions that require further intervention. This study emphasizes the importance of holistic and gender-sensitive interventions, as well as the need for collaboration between governments, non-governmental organizations, and communities to create a safe and supportive environment for street children